Duodenal mucosal immune cells in treatment-naive adult patients with celiac disease having different histological grades and controls - Gaurav P S. Gahlot; Prasenjit Das; Vandana Baloda; Alka Singh; Sreenivas Vishnubhatla; Siddhartha Datta Gupta; Govind K Makharia (Wolters Kluwer Medknow Publications, 2019)
Background: It is hypothesized that the duodenal mucosal damage in patients with celiac disease (CeD) is caused by the mucosa-infiltrating lymphoid cells. This study aimed to analyze the immune effective and regulatory T (Treg) cells in duodenal biopsies from treatment-naive adult patients with CeD having different histological grades and controls. Patients and Methods: Dual-color immunohistochemical staining was done in a total of 234 duodenal biopsies, including 132 controls and 102 adult patients with CeD using CD20, CD3:CD4, CD3:CD8, CD4:FoxP3, CD8:FoxP3, and TCRαβ:TCRγδ antibodies. The density of these lymphoid cells in lamina propria and mucosal epithelium was compared between controls and CeD, with different modified Marsh grades. Results: Densities of CD4+ T cells in lamina propria and CD8+γδ intraepithelial lymphocytes (IELs) were significantly more in biopsies from patients with CeD, than in controls. An increasing linear pattern of IELs, CD3+ T cells, and CD20+ B cells was observed with increasing grades of villous abnormalities. Although CD8+ FoxP3+ Treg cells were significantly more in biopsies from patients with CeD, there was no significant difference in CD4+ FoxP3+ Treg cell infiltrate between both the groups. Conclusion: Our finding in this observational study generates interest to study the local intestinal mucosal immunity in CeD in detail. A study to prove the failure of CD4+ FoxP3+ Treg cell recruitment in CeD and its direct functional impact may yield valuable information regarding loss of mucosal tolerance.